Strength of the Uninvolved Limb Following Return to Activity After ACL Injury: Implications for Symmetry as a Marker of Sufficient Strength - Matthew T Hartshorne; Jeffrey A Turner; Kenneth L Cameron; Darin A Padua (North American Sports Medicine Institute, 2024)
# Background Muscular strength deficits are common after ACL injury. While the Limb Symmetry Index (LSI), using the uninvolved limb as a reference, is widely used, negative strength adaptations may affect both limbs post-injury. It is uncertain how the strength of the uninvolved limb in those with an ACL injury compares to uninjured individuals, making it unclear whether it is appropriate as a benchmark for determining sufficient strength. # Purpose To compare the strength of key lower extremity muscles of the uninvolved limb in those with history of ACL injury (ACL-I) to the dominant limb in individuals with no history of ACL injury (control). # Study Design Cross-sectional study. Methods: A total of 5,727 military cadets were examined, with 82 females and 126 males in the ACL-I group and 2,146 females and 3,373 males in the control group. Maximum isometric strength was assessed for six muscle groups measured with a hand-held dynamometer. Separate two-way ANOVAs with limb and sex were performed for each muscle group. # Results Significant main effects for limb were observed with the uninvolved limb in the ACL-I group displaying greater strength compared to the dominant limb in the control group for the quadriceps, hamstrings, and gluteus medius, but effect sizes were small (Cohen's d <0.25). Significant main effects for sex were observed with greater male muscular strength in all six muscle groups with small to large effect sizes (Cohen's d 0.49-1.46). No limb-by-sex interactions were observed. # Conclusions There was no evidence of reduced strength in the uninvolved limb in those with a history of ACL injury compared to the dominant limb in those with no prior ACL injury. This finding suggests that, after clearance to return to activities, the uninvolved limb can be used as a standard for comparison of sufficient strength, including when using the LSI. Level of Evidence: Level 3